PROFILE OF WOMEN WITH INDUCED ABORTION COMPLICATIONS IN NIGERIA: Life Science-Family Medicine - VINCENT OGHENEKOBARO, DR. AWUSI (International Journal of Life Science and Pharma Research, 2012)
Background: Complications of induced abortion remain significant causes of maternal mortality and morbidity globally, particularly in countries, such as Nigeria, that do not provide access to safe abortion services. Aim: The aim of this retrospective study was to determine the socio-demographic characteristics of 180 women who were treated for post-induced abortion complications. Design: This was a retrospective study. Setting: Delta State University Teaching Hospital, Warri (temporary site), Nigeria. Subjects: Women treated for various cases of abortion complications over a 3year period, January 1st 2006 to December 31st 2008. Results : Majority of the respondents were aged 15 – 24years (69%) and presented themselves for abortion when the pregnancy was more than 12weeks( 34% ); were unmarried( 66% ), attained (or about to attain ) at least secondary education( 86% ), dependants –students/applicants( 80% ). The chief reason for procuring an induced abortion was the desire to complete school or training( 45% ) .Post-induced abortion contributed significantly to the maternal morbidity( 9.68% ) and mortality( 0.43% ) in this study. Conclusion: The study shows that induced abortion is mainly undertaken by teenagers who are mainly students/apprentices and the main reason of procuring abortion was to complete school or training. . Health and social workers could use the social profile obtained from this study as a guide to identify women at risk of unwanted pregnancy, consequent induced/unsafe abortion, and formulate preventive- initiatives targeted at them.